2011
DOI: 10.1007/s00430-011-0225-y
|View full text |Cite|
|
Sign up to set email alerts
|

Febrile response induced by cecal ligation and puncture (CLP) in rats: involvement of prostaglandin E2 and cytokines

Abstract: The purpose of the present study was to better understand the events involved in the febrile response induced by cecal ligation and puncture (CLP), a complex infectious process. To this end, we conducted in vivo experiments in rats examining (1) fever development, (2) bacterial number in the infection focus and in blood, (3) peripheral and hypothalamic synthesis of cytokines, (4) hypothalamic and cerebrospinal fluid (CSF) synthesis of prostaglandin E(2) (PGE(2)), (5) the effect of anti-IL-6 antibody on fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
2
9
0
2
Order By: Relevance
“…In the hippocampus and brainstem, only IL-1β protein returned to baseline before the 72 h sample. These findings of an early increase in cytokine protein in mouse brain are consistent with those of a recent study demonstrating increased IL-1β, IL-6 and TNF in hypothalamus of rats as early as 3 – 6 h post CLP (Figueiredo et al 2012). The brain heterogeneity with respect to cytokine responses to CLP may have functional relevance due to the generalized roles of the hypothalamus, hippocampus and brainstem in different physiological and behavioral processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the hippocampus and brainstem, only IL-1β protein returned to baseline before the 72 h sample. These findings of an early increase in cytokine protein in mouse brain are consistent with those of a recent study demonstrating increased IL-1β, IL-6 and TNF in hypothalamus of rats as early as 3 – 6 h post CLP (Figueiredo et al 2012). The brain heterogeneity with respect to cytokine responses to CLP may have functional relevance due to the generalized roles of the hypothalamus, hippocampus and brainstem in different physiological and behavioral processes.…”
Section: Discussionsupporting
confidence: 91%
“…Additional studies with better spatial resolution of cytokine upregulation in brain are necessary before definitive conclusions may be made. It is clear, however, that cytokines are critical mediators of CNS responses to sepsis [e.g., (Gourine et al, 1998; Leon et al, 1998; Figueiredo et al, 2012)]. Previous studies demonstrate that TNF is a key mediator of temperature responses of mice to sepsis, whereas IL-6 is implicated in fever and food intake (Leon et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, TNFRI knockout mice developed a febrile response similar to wild‐type mice after sepsis, suggesting that this receptor is not important for the febrile response in this condition . It should be noted that, particularly in sepsis, the febrile response depends on a massive release of several mediators , which may compensate for the lack of TNF‐α signalling. Alternatively, Roby et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to reinforce our hypothesis, we developed an experimental strategy to block the IL‐6 action specifically in the third ventricle of the hypothalamus during the exercise by anti‐IL‐6 ICV injections. This approach has been extensively used to block the central action of this cytokine in rodents (Figueiredo et al, ; Le Foll et al, ; Palin et al, ; Timper et al, ). Interestingly, our study demonstrated the anti‐IL‐6 ICV injections, partially reduced the anorexigenic effects of exercise in mice.…”
Section: Discussionmentioning
confidence: 99%